Cinnabar-induced hormesis in Trichoderma longibrachiatum MD33: multi-omics elucidation of a fungal-specific dendrobine biosynthesis pathway - Jain, Archana; Sarsaiya, Surendra; Gong, Qihai (Frontiers in Microbiology, 2025)
IntroductionThe endangered orchid Dendrobium nobile is the primary source of dendrobine, a neuroprotective sesquiterpene alkaloid, but unsustainable harvesting necessitates alternative production platforms, such as the endophytic fungus Trichoderma longibrachiatum MD33. However, the fungal dendrobine pathway and its regulatory mechanisms remain uncharacterized, limiting its biotechnological exploitation.MethodsThis study investigated cinnabar (HgS)-induced hormesis to elucidate the stress-mediated metabolic reprogramming of dendrobine biosynthesis through integrated transcriptomic and metabolomic profiling.ResultsSubtoxic HgS concentrations (1.0–4.0 μg/L) triggered ROS signaling, upregulating the mevalonate pathway, terpenoid synthases (TPS1/2), and cytochrome P450 monooxygenases (CYP450s), thereby enhancing dendrobine yields by 24% at 4.0 μg/L. In contrast, cytotoxic doses (6.0 μg/L) suppressed growth (73.9% inhibition) and dendrobine synthesis (73.2% reduction), correlating with metabolic collapse via disrupted CoA biosynthesis and antioxidant depletion. Multi-omics integration revealed biphasic regulation: low HgS activated stress-responsive transcription factors (bZIP, Zn-Cys6) and MAP kinase cascades, redirecting resources toward dendrobine production, whereas high HgS induced apoptotic markers and oxidative damage.ConclusionThese findings establish 4.0 μg/L a hormetic threshold for maximizing dendrobine yields and delineating the genetic and enzymatic architecture of its fungal biosynthesis. This work provides a roadmap for the metabolic engineering of T. longibrachiatum MD33, emphasizing ROS-mediated pathway optimization for sustainable alkaloid production. Future studies should leverage CRISPR-based editing of identified regulatory nodes (e.g., HMGR and FPPS) to enhance stress resilience and dendrobine titers in industrial strains.